Peran Kepemimpinan Transformasional Kepala Sekolah dalam Meningkatkan Kualitas Pendidikan Islam - Mubasyiroh, Nabilatun; Muttaqin, M Imamul (Jurnal Pendidikan Islam, 2024)
Islamic education has faced several challenges due to developments over time. In facing this, every Islamic educational institution must choose a leadership model that is effective in advancing Islamic education. Transformational leadership focuses on change through inspiring, motivating and empowering. So that transformational leadership can be a solution in dealing with these problems. This research examines the role of transformational leadership in improving the quality of Islamic education. Islamic education leaders do not only focus on structural development, but also shape the character of students in accordance with Islamic teachings.  It is hoped that the results of this research will enable educational leaders to understand the leadership roles needed at this time. The aim of this research is to determine the application and role of school principals' transformational leadership in improving the quality of Islamic education along with the factors that influence the application of transformational leadership in Islamic education. The method used in this research is a literature study using secondary data in data collection. So that the result is transformational leadership, the principal is not only a structural leader but also supports and motivates his members in accordance with organizational goals. In transformational leadership, school principals must apply 4 principles, namely ideal influence, inspirational motivation, intellectual simulation and individual attention. In transformational leadership there are factors that encourage and inhibit its implementation, namely openness of information between the principal and school members as well as adequate infrastructure and human resources. Apart from the driving factors, there are also inhibiting factors, namely the lack of training for teachers and the unwillingness of school members to develop with modern times.